Uji Pengaruh Pupuk Organik Vermiwash dan Patogenisitas Pupuk Hayati VP3 Terhadap Enam Bibit Tanaman - Miftahur Rohmah; S Sunawan; Novi Arfarita (Folium : Jurnal Ilmu Pertanian, 2020)
Biofertilizer are formulas made from active ingredients of living organisms or latent (microbial), usually in liquid or solid form, have the ability to mobilize, facilitate and increase nutrient availability through biological processes that are not available into available forms. The aims of this research is to determine differences in growth after application of vermiwash and pathogenic effect of VP3 biofertilizer to six plant seeds: soybeans, long beans, chickpeas, kale, mustard greens, and spinach. This research was conducted at the Microbiology Laboratory of Malang Islamic University from March to May 2020. This research uses a Complete Randomized Design (CRD) with 3 treatments and it was repeated 6 times. This research suggests that the treatment of VP3 biofertilizer gave better results compared to other treatments on the parameters of seed height and fresh weight of plant seedlings tested. However, the kale gave a real effect only on seed height parameters and the application of VP3 biofertilizer did not show any signs of pathogenicity such as necrosis, wilting, root rot or stem tot on the six seedlings tested. Keywords : VP3 Biofertilizers, vermiwash, soybeans, long beans, chickpeans, kale, mustard green, spinach